Pengaruh Pemberdayaan Sumber Daya Manusia dan Lingkungan Kerja terhadap Kinerja Pegawai di Kantor Wilayah Kementerian Hukum dan HAM (Kemenkumham) Manokwari - Rohana, Dwi Kristika; Hafel, Muhlis; Purwanto, Purwanto (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2024)
This study examines the impact of human resource (HR) empowerment and the work environment on employee performance at the Regional Office of the Ministry of Law and Human Rights in Manokwari. The research addresses the critical importance of HR empowerment and a conducive work environment in enhancing employee productivity and efficiency. The study utilizes a quantitative survey method, distributing questionnaires to 100 employees, with the collected data analyzed through multiple linear regression to determine the influence of the independent variables on the dependent variable. Results indicate that both HR empowerment and the work environment significantly and positively affect employee performance. The study concludes that improving HR empowerment and work conditions are vital strategies for boosting performance in government agencies. Recommendations include the implementation of continuous empowerment programs and the enhancement of work facilities to further improve employee performance and overall organizational effectiveness.